Harnessing Creative Technology for Social Entrepreneurship: Innovations in Virtual Reality and Augmented Reality for Community Development - Barroso, Uwe; Xavier, Murphy; Elliot, McCarty (Journal of Social Entrepreneurship and Creative Technology, 2024)
The intersection of creative technology and social entrepreneurship presents new opportunities for community development. Virtual Reality (VR) and Augmented Reality (AR) technologies have the potential to create immersive experiences that can address social issues and foster sustainable development. Despite the growing interest in these technologies, there is a lack of comprehensive research on their application in social entrepreneurship. This study aims to explore how innovations in VR and AR can be harnessed to support social entrepreneurship initiatives focused on community development. The research seeks to identify best practices, challenges, and the impact of these technologies on social businesses. A mixed-methods approach was employed, combining qualitative and quantitative research. The qualitative phase involved interviews with social entrepreneurs who have integrated VR and AR into their projects. The quantitative phase included surveys to measure the impact of these technologies on community engagement and development. Case studies of successful implementations were also analyzed to provide practical insights. The findings reveal that VR and AR technologies significantly enhance community engagement and participation in social entrepreneurship projects. Social entrepreneurs reported improved outreach, better visualization of social issues, and increased empathy among participants. Quantitative data showed a positive correlation between the use of these technologies and the effectiveness of community development initiatives. Innovations in VR and AR offer promising tools for social entrepreneurs aiming to create positive social impacts. These technologies enhance the ability to engage communities and address complex social issues. Future research should focus on scaling these innovations and exploring their long-term effects on sustainable development.